Strategi Pengelolaan Masjid Ka’bah di Mulyoharjo Jepara sebagai Destinasi Wisata Religi - Dimas Saputra, Afen; Nafi’, Ahmad (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2025)
The Kaaba Mosque in Mulyoharjo, Jepara, is unique because its design resembles the Kaaba in Mecca. Therefore, in addition to being a place of worship, it has also developed as a religious tourism destination that attracts public attention. This condition demands an appropriate management strategy so that the main function of the mosque as a centre of worship is maintained while being able to provide benefits to worshippers and tourists. This study aims to describe the management strategy of the Kaaba Mosque as a religious tourism destination by emphasizing the balance between religious, social, and tourism aspects. The research method used is qualitative with a descriptive approach, namely by describing the conditions that occur in the field (field research), data collection through interviews, observation, and documentation. Data analysis was carried out through the process of data reduction, data presentation, and drawing conclusions, while data validity was obtained through triangulation and discussions with related parties. The results of the study indicate that the management of the Kaaba Mosque is carried out through organizing religious activities that maintain the solemnity of worship, managing services to worshippers and tourists that emphasize comfort and educational value, and empowering the surrounding community to support the sustainability of religious tourism.